The Safety and Efficacy of Combining Saxagliptin and Pioglitazone Therapy in Streptozocin-Induced Diabetic Rats - Ahmed Mohamed Othman; Ibrahim Ashour Ibrahim; Samy M. Saleh; Dina M. Abo-Elmatty; Noha M. Mesbah; Asmaa R. Abdel-Hamed (Biomedicines, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a chronic progressive disease due to insulin resistance. Oxidative stress complicates the etiology of T2DM. Saxagliptin is a selective dipeptidyl peptidase-4 (DPP-4) inhibitor, while Pioglitazone is a thiazolidinedione insulin sensitizer. This study aimed to assess the effect of Saxagliptin and Pioglitazone monotherapy and combination therapy on the biochemical and biological parameters in streptozotocin (STZ)-induced diabetic rats. Methods: The study included thirty-five male albino rats. Diabetes mellitus was induced by intraperitoneal STZ injection (35 mg/kg). For a 1-month duration, rats were divided into five groups. Glucose homeostasis traits, lipid profiles, kidney functions, liver enzymes, and oxidative stress markers were measured. Gene expression of miRNA-29a, phosphoenolpyruvate carboxykinase (PEPCK), phosphoinositide-3-kinase (PI3K), and interleukin 1 beta (IL-1β) was assessed using qRT-PCR. Results: At a 1-month treatment duration, combination therapy improves oxidative stress markers more than either drug alone. The combination therapy had significantly higher levels of SOD, catalase, and GSH and lower levels of MDA compared to the monotherapy. Additionally, the diabetic group showed a significant increase in the expression levels of miRNA-29a, PEPCK, and IL-1β and a significant decrease in PI3K compared to the normal control group. However, combination therapy of Saxagliptin and Pioglitazone was more effective than either Saxagliptin or Pioglitazone alone in reversing these results, especially for PEPCK and IL-1β. Conclusions: Our findings revealed that combining Saxagliptin and Pioglitazone improves glycemic control and genetic and epigenetic expression profiles, which play an essential regulatory role in normal metabolism.